2016
DOI: 10.1111/jfb.12956
|View full text |Cite
|
Sign up to set email alerts
|

Genotyping of microsatellite markers to study genetic structure of the wild striped snakehead Channa striata in Malaysia

Abstract: Genetic variability and differences in wild striped snakehead Channa striata from Malaysia were analysed by genotyping nine novel nuclear microsatellite loci. Analysis revealed moderate-to-high genetic diversity in most of the populations, indicative of large effective population sizes. The highly diversified populations are admixed populations and, therefore, can be recommended as potential candidates for selective breeding and conservation since they each contain most of the alleles found in their particular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 59 publications
3
8
0
Order By: Relevance
“…Per population estimates of genetic diversity of C. striata in this study (Table 3; overall A R = 4.23, range of A R : 3.00-5.20; overallĤ E = 0.53, range ofĤ E : 0.43-0.67) were within the spectra of diversity estimates reported for populations in the Mekong River Basin (Adamson et al, 2012; overall A R = 4.04, range of A R : 2.04-4.94, overall H E = 0.67, range ofĤ E : 0.34-0.77) and throughout Malaysia (Tan et al, 2016: overall A R = 4.76, range of A R : 3.00-7.63, overallĤ E = 0.58, range ofĤ E : 0.3-0.76). Tan et al (2016) study also quantified intra-population diversity of C. striata in Papar (A R = 4.29,Ĥ E = 0.55) and Kota Belud (A R = 3.00,Ĥ E = 0.36), which were roughly similar with our measurements (Papar: A R = 4.75,Ĥ E = 0.50; Kota Belud: A R = 3.77,Ĥ E = 0.43). We attribute slight discrepancies in these estimates to differences in the number of markers and sample sizes, which are more parsimonious than citing temporal variations as sampling periods in both independent assessments were overlapping: between 2007 and 2010 in Tan et al (2016) and between 2010 and 2013 in this study.…”
Section: Inferences On Genetic Diversitysupporting
confidence: 80%
See 3 more Smart Citations
“…Per population estimates of genetic diversity of C. striata in this study (Table 3; overall A R = 4.23, range of A R : 3.00-5.20; overallĤ E = 0.53, range ofĤ E : 0.43-0.67) were within the spectra of diversity estimates reported for populations in the Mekong River Basin (Adamson et al, 2012; overall A R = 4.04, range of A R : 2.04-4.94, overall H E = 0.67, range ofĤ E : 0.34-0.77) and throughout Malaysia (Tan et al, 2016: overall A R = 4.76, range of A R : 3.00-7.63, overallĤ E = 0.58, range ofĤ E : 0.3-0.76). Tan et al (2016) study also quantified intra-population diversity of C. striata in Papar (A R = 4.29,Ĥ E = 0.55) and Kota Belud (A R = 3.00,Ĥ E = 0.36), which were roughly similar with our measurements (Papar: A R = 4.75,Ĥ E = 0.50; Kota Belud: A R = 3.77,Ĥ E = 0.43). We attribute slight discrepancies in these estimates to differences in the number of markers and sample sizes, which are more parsimonious than citing temporal variations as sampling periods in both independent assessments were overlapping: between 2007 and 2010 in Tan et al (2016) and between 2010 and 2013 in this study.…”
Section: Inferences On Genetic Diversitysupporting
confidence: 80%
“…With respect to current knowledge on the phylogeographical structuring of C. striata, the connectivity of the palaeodrainage in the Sunda plains may well be extended from west Borneo (Sarawak, Malaysia) to its northwest (west coast of Sabah). The earlier proposition that C. striata populations throughout the Malaysian Borneo are homogeneous (Tan et al, 2012(Tan et al, , 2016 is refuted herein as more comprehensive sampling revealed that the east Sabah populations constitute a distinct clade altogether. Concurrently, our findings echo the claim by Inger and Chin (1962) such that a "large part" of North Borneo (i.e., the northeastern region) was isolated (or became disconnected due to saline intrusion much earlier) from the palaeo-river system that previously connected a large expanse of freshwater ecosystems in the Sunda shelf.…”
Section: Phylogeography and Genetic Structuring Of C Striata In Sabahmentioning
confidence: 76%
See 2 more Smart Citations
“…Moreover, they have been widely developed and used in the study of population genetics of many species (Guo et al, 2016;Mohanty et al, 2016;Tan et al, 2016). Furthermore, some of these microsatellite markers developed for Scomber species have been successfully used for amplification in other related species (Tang et al, 2009;Divya et al, 2016).…”
Section: Introductionmentioning
confidence: 99%